Characteristics of patients presenting with septic wounds in selected hospitals in Kajiado County, Kenya - Kaanto, Ruth; Kagira, John; Waititu, Kenneth; Ngotho, Maina; Maina, Naomi; Gachohi, John (International Journal Of Community Medicine And Public Health, 2021)
Background: Wound management is a serious global health problem. The objective of this study was to describe the characteristics of patients presenting with septic wounds in selected hospitals in Kajiado County, Kenya, and their association with selected factors. Methods: We purposively sampled 182 patients with septic wounds and collected data using questionnaires whose statistical relationship between various patients' characteristics, including the data collected Likert-scale design was assessed. Results: A majority (73.1%) of the patients presented with one wound. Most (54.4%) of the wounds were located on the lower limbs and mainly (23.1%) caused by road traffic accidents. The majority of the wounds had lasted for 1-2 weeks at the time of presentation, and the wound sizes were mainly >11 mm. We found a significant association (p<0.05) between number of wounds and age, marital status, and highest education level. The wound causes were significantly associated with gender, age, occupation, and sub-county of residence. Wound duration was significantly associated with understanding prescribed medication, adherence to dosage, water source, alcoholism, and cigarette smoking. Wound improvement was significantly associated with patients' understanding of the prescribed medication, adherence to dosage and water source, alcoholic status, and cigarette smoking. Conclusions: Individual patient, social and cultural factors were associated with septic wounds characteristics, suggesting that addressing them at the individual level using proper hygiene and cleanliness at home and workplaces is key. Policies to reduce traffic accidents, increase literacy, and promote healthcare access need to be promoted to reduce the wound sepsis burden.